Into the still blue - Rossi, Veronica (New York, NY Harper, an imprint of HarperCollinsPublishers, 2014)
In their effort to reach the fabled Still Blue, Aria and Perry will have to rescue Cinder, defeat Sable and Hess, and unite the Dwellers and the Outsiders once and for all--Provided by publisher.
Donated by Jowana B. Bueser
Keywords: Science fiction